PENGARUH BELANJA MODAL DAN PENYERTAAN MODAL PEMERINTAH TERHADAP TINGKAT KEMANDIRIAN DAERAH PADA SELURUH KAB/KOTA DI KALIMANTAN TIMUR TAHUN 2013-2017 - Muhammad Kadafi, SE., M.SA; Oemar Dhanny; Dewi Wahyuni (Jurnal Eksis, 2019)
The purpose of this research to know the level of regional financial indepedence in all city districts in the Province of East Kalimantan period of 2013-2017. This research use secondary data, namely reports on the realization of regional income that are focused in capital expenditure and government equity capital in all city districs in the province of East Kalimantan obtain from Financial Management Board and The Regional Assets period 2013-2017. This research use multi linier regression of parametic statistic analithycal method. The results showed:1) Based on partialy capital expenditure does not have a significant effect on the level of local independence. 2) Based on partialy government equity capital is positively influenced isn’t significant effect to the level of local independence. 3) Capital expenditure and government equity capital based on sumultaneous (f-test) doesn’t have a significant effect to the level of local independence in all city districts in the province of East Kalimantan. Keywords: Capital Expenditure, Government Equity Capital and The Level of District independence.